PENGARUH EFISIENSI MODAL INTELEKTUAL TERHADAP KINERJA PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI MODERASI - Robby Krisyadi; Hendi Hendi; Saltycia Chairika (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2024)
This study aims to investigate the impact of intellectual capital on the performance of companies listed on the Indonesia Stock Exchange with the moderation of company size. The research focuses on the use of quantitative data, including the annual reports of companies listed on the IDX from 2018 to 2022. The sample was collected using purposive sampling method, comprising a total of 166 company samples. The analytical methods employed include classic assumption testing, multiple linear regression analysis, and hypothesis testing using the F-test (for overall influence) and the t-test (for partial influence) at a significance level of 0.05. The results of this study reveal an insignificant relationship between intellectual capital (MVAIC) and company performance (ROA) as well as company size gives insignificant to the relationship. This finding provides valuable insights for stakeholders in the Indonesian stock market and companies listed on the Indonesia Stock Exchange in managing their intellectual capital.